Detectable ctDNA at the time of treatment cessation of ipilimumab and nivolumab for toxicity predicts disease progression in advanced melanoma patients - Warburton, Lydia; Reid, Anna; Amanuel, Benhur; Calapre, Leslie; Millward, Michael; Gray, Elin (Frontiers in Oncology, 2023)
Background Immune checkpoint inhibition (ICI) has led to unprecedented outcomes for melanoma patients but is associated with toxicity. ICI resumption after high grade irAEs poses a significant challenge in the clinical management of melanoma patients and there are no biomarkers that can help identify patients that might benefit from resuming treatment. This study aims to determine if circulating tumor DNA (ctDNA) levels at the time of treatment-limiting irAE could guide treatment decisions in this clinical context. Methods This is a retrospective exploratory biomarker study from 34 patients treated with combination ICI for stage IV melanoma. Patients had a treatment-limiting toxicity and a baseline plasma collection prior to commencing ICI and within 6 weeks of stopping therapy. Blood samples were tested for ctDNA at baseline and cessation therapy. Results Median progression free survival (PFS) and overall survival (OS) have not been reached (24-month PFS rate 54% and OS rate 72.3%). PD occurred in 47% (16/34) of patients. Median PFS with detectable ctDNA from plasma collected at the time of toxicity was 6.5 months while not reached (NR) with undetectable levels (HR: 4.0, 95% CI 0.95-17.5, p=0.0023). Median OS with detectable ctDNA at cessation for toxicity was 19.4 months and NR for undetectable ctDNA (HR: 3.9, 95%CI 20.8-18.6, p=0.024). Positive ctDNA at the time of cessation was highly specific (specificity 0.94, 95% CI 0.74-0.99, PPV 0.88, 95% CI 0.53-0.99). However, ctDNA negativity has low sensitivity as a predictor of ongoing disease control (sensitivity 0.437, 95% CI 0.23-0.67). Notably, 4/9 (44%) ctDNA negative patients who had disease progression had brain only disease progression. Conclusions Undetectable ctDNA and CR on imaging after stopping immunotherapy for toxicity results in high rates of long-term durable control. For patients with immunotherapy related toxicity, who have persistent ctDNA at 8 – 12 weeks, the risk of disease progression is significant.